THE INFLUENCE OF NURSE EDUCATION LEVEL ON HOSPITAL READMISSIONS - Tarfa Mohammed Faiz Alamri; Mishriya Rasheed Abdullah Alsaloli; Muneerah Rasheed Abdullah Alsaloli; Mai Ibrahim Najem Alsaadi; Khazma Mohammad Alihayan Alsaloli; Salha Mesfer Feheed Alsaloli; Haya Ali Almuaili; Nasser Mufreh Salamah Al-Nusairi; Mohammed Sihman Alsharari; Adel Maqbul Alsharari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Hospital readmissions are a significant concern globally, with rates varying across different healthcare systems. In Poland, the readmission rate for patients returning to the same hospital and ward within 30 days is notably high at 19.2%. The lack of continuity of care between in-hospital and post-hospital settings is a key risk factor for readmissions, with studies indicating that a substantial percentage of patients do not adhere to discharge recommendations due to inadequate communication between inpatient and outpatient care providers. Preventing readmissions has become a priority in healthcare policy, with financial penalties imposed in some countries to incentivize hospitals to reduce readmission rates. Objective: This research aims to investigate the relationship between nurse education level and hospital readmission rates. The objectives include assessing the impact of nurse education on patient outcomes and care quality, identifying potential disparities in readmission rates based on nurse education level, exploring the role of nurse education in reducing healthcare costs related to readmissions, and identifying strategies to enhance nurse education levels to improve patient care. Conclusion: Nurse education plays a critical role in reducing hospital readmission rates and enhancing patient outcomes. Nurses with higher levels of education are better equipped to provide quality care, engage in evidence-based practice, facilitate effective communication and collaboration within healthcare teams, and empower patients through education and self-management skills. Factors influencing nurse education level and readmission rates are interconnected, underscoring the importance of investing in nurse education to elevate the overall quality of patient care. Strategies such as continuous professional development, promoting academic achievement, and fostering collaboration with academic institutions can aid in increasing nurse education levels and driving positive changes in healthcare delivery to benefit both nurses and patients. Prioritizing nurse education can lead to improved healthcare outcomes and decreased readmission rates.